Pengaruh Kepemimpinan Kepala Sekolah dan Budaya Sekolah terhadap Organizational Citizenship Behavior (OCB) Guru SMP Negeri Se-Kecamatan Batang - Prasetya, Candra; Murniati, Ngurah Ayu Nyoman; Prayito, Muhammad (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The background to this research problem is related to the organizational citizenship behavior (OCB) of state junior high school teachers in Batang District in the dimensions of altruism, conscientiousness, sportsmanship, courtesy and civic virtue. The principal's leadership and school culture are expected to improve teachers' organizational citizenship behavior (OCB). Based on the explanation above, research was carried out to analyze the influence of principal leadership and school culture on organizational citizenship behavior (OCB) of state junior high school teachers in Batang District. This research aims to examine and analyze: (1) the influence of the principal's leadership on teachers' organizational citizenship behavior (OCB), (2) the influence of school culture on teachers' organizational citizenship behavior (OCB), (3) the simultaneous influence of the principal's leadership and culture schools on teachers' organizational citizenship behavior (OCB). Population 273 people, sample of 160 people. The instrument test used is the validity and reliability test. Test classical assumptions/prerequisites using the normality test, linearity test, homogeneity test, and heteroskedastisity test. Data analysis used regression test, F test (ANOVA) and t test. Based on the research results, it can be concluded as follows: (1) the principal's leadership has a positive and significant effect on the organizational citizenship behavior (OCB) of State Middle School teachers in Batang District, as proven by a Sig value of 0.003 < 0.05 and tcount 6.425 > ttable 1.975. The magnitude of the influence of X1 on Y is 72.6%; (2) school culture has a positive and significant effect on the organizational citizenship behavior (OCB) of state junior high school teachers in Batang District as proven by the Sig value of 0.000 < 0.05 and tcount 7.783 > ttable 1.975. The magnitude of the influence of X2 on Y is 63.1%; (3) the principal's leadership and school culture simultaneously have a positive and significant effect on teachers' organizational citizenship behavior (OCB), as proven by the Fcount value of 43.952 > Ftable 3.050 with a significance level of 0.010 < 0.05. The magnitude of the influence of X1 and X2 is 70.2%. The suggestions put forward by researchers are: (1) for school principals, it is hoped that they will improve their leadership, especially in the instructive dimension, encourage the creation of a school culture in the dimension of attention to detail, and encourage increased organizational citizenship behavior (OCB) of teachers in the altruism dimension (2) for teachers , it is recommended to improve organizational citizenship behavior (OCB), especially in the altruism dimension, and get used to communicating with other teachers if they experience difficulties at work, especially in identifying students' learning conditions.